Characteristics of avoidant/restrictive food intake disorder in a general paediatric inpatient sample. (22nd October 2020) - Schöffel, Hannah; Hiemisch, Andreas; Kiess, Wieland; Hilbert, Anja; Schmidt, Ricarda
Abstract: Objective: Although patients with avoidant/restrictive food intake disorder (ARFID) often consult general paediatric services initially, existing literature mostly concentrated on intensive eating disorder treatment settings. This cross‐sectional study sought to describe symptoms of ARFID and their associations with eating disorder psychopathology, quality of life, anthropometry, and physical comorbidities in a general paediatric sample. Methods: In N = 111 patients (8–18 years) seeking treatment for physical diseases, prevalence of ARFID‐related restrictive eating behaviours was estimated by self‐report and compared to population‐based data ( N = 799). Using self‐report and medical record data, further ARFID diagnostic criteria were evaluated. Patients with versus without symptoms of ARFID based on self‐report and medical records were compared in diverse clinical variables. Results: The prevalence of self‐reported symptoms of ARFID was not higher in the inpatient than population‐based sample. Only picky eating and shape concern were more common in the inpatient than population‐based sample. Although 68% of the inpatient sample reported any restrictive eating behaviours, only 7% of patients showed symptoms of ARFID based on medical records in addition to self‐report, particularly those with underweight, without significant effects for age, sex, and medical diagnoses. Discussion: The study revealed the importance of considering ARFID within the treatment of children and adolescents with physical diseases, especially for those with underweight. Further research is needed to replicate the findings with interview‐based measures and to investigate the direction of effects in ARFID and its physical correlates. Highlights: Prevalence of ARFID‐related restrictive eating behaviours was not higher in a general paediatric inpatient setting compared to a general population sample, but only in combination with objectively measured underweight Prevalence of symptoms of ARFID based on self‐report and medical records was 7.2% in a general paediatric sample, without differences between diverse medical diagnoses